Stronger Utility - Pavlo R. Blavatskyy (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2011)
Empirical research often requires a method how to convert a deterministic economic theory into an econometric model. A popular method is to add a random error term on the utility scale. This method, however, violates stochastic dominance. A modification of this method is proposed to avoid violations of dominance. The modified model compares favorably to other existing models in terms of goodness of fit to experimental data. The modified model can rationalize the preference reversal phenomenon. An intuitive axiomatic characterization of the modified model is provided. Important microeconomic concept of risk aversion is well-defined in the modified model.
Keywords: C25; D03; D81; 330; Decision Theory; Probabilistic Choice; Stochastic Dominance; Strong Utility; Risk Aversion